The longer-term costs and benefits of different initial teacher training routes - Rebecca Allen; Chris Belfield; Ellen Greaves; Caroline Sharp; Matt Walker (Institute for Fiscal Studies (IFS), 2016)
Teacher recruitment and retention are increasingly challenging for schools as the pools of graduates in key subjects decline and pupil numbers grow. This report reveals around 40% of teachers who begin their initial training are not in a state school job five years later. That means of 35,000 or so individuals training to become teachers each year some 14,000 are not teaching five years later. Initial teacher training is expensive, costing an average of 23,000 per trainee taking into account costs to government and schools. The high drop-out rate means that on average more than 38,000 is spent on training for every teacher still in post five years after completing training. This research, funded by the Nuffield Foundation, also shows how routes into teaching have changed in recent years, and looks at the costs, benefits and retention rates for each route. School-led routes have grown quickly, with "School Direct" accounting for around one-third of trainees in 2015-16. Teach First has also expanded now accounting for 5% of entrants, although more than 40% of trainees are still trained through traditional university-led postgraduate courses.
Keywords: 330